Hoạt động đổi mới và phát triển tài chính: Bằng chứng thực nghiệm tại một số quốc gia Đông Nam Á - Nguyễn Hoàng, Minh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
This article aims to explore the relationship between financial development and innovation in selected Southeast Asian countries (Vietnam, Singapore, Thailand, Indonesia, Malaysia, Bruney, Philippines). The data were collected from the World Intellectual Property Organization, International Monetary Fund, World Bank, with Pooled OLS, random-effects, and fixed-effects methods were used. The research results show that financial institution development has a positive impact on the innovation activities of some Southeast Asian countries as well as the economic development is a factor which promotes the renovation activities of some Southeast Asian countries. In addition, the innovation activities of some Southeast Asian countries are still very low. Based on the research result, Southeast Asian countries need to have appropriate policies to develop financial institutions, especially focus on developing bank credit for the private sector in an economy, facilitating the innovation activities of the private sector.